Money and prices: An I(2) analysis for the euro area - Oliver Holtemöller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
The concept of integrated stochastic processes is widely used in empirical macroeconomics; and cointegration analysis is an important framework to analyze economic time series both in single equation and in system approaches. This framework is not only suited to study the relationships between variables that are integrated of order one, denoted by I(1), but also to analyze variables that are integrated of higher order. However, in the literature the analysis of I(1) models is much more popular than the analysis of I(2) models although there is some evidence that relevant economic times series like nominal money and the price level in the euro area are integrated of order two. This is confirmed by applying tests on double unit roots. The purpose of this paper is to illustrate the analysis of I(2) variables and to show how this technique can be applied to explore the relationship between money and prices. The leading indicator property of money for prices, money demand analysis and the role of money in the transmission mechanism are addressed. It turns out that the I(2) analysis provides a considerable empirical method for extracting information from monetary aggregates for monetary policy purposes.
urn:nbn:de:kobv:11-10048611
Keywords: C22; C32; E41; 330; cointegration; Double unit roots; I(2) model; euro area money demand